2017
DOI: 10.1107/s2052520617008617
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of charge-shift bond in fluorite CaF2

Abstract: On the basis of a multipole refinement of single-crystal X-ray diffraction data collected using an Ag source at 90 K to a resolution of 1.63 Å, a quantitative experimental charge density distribution has been obtained for fluorite (CaF). The atoms-in-molecules integrated experimental charges for Ca and F ions are +1.40 e and -0.70 e, respectively. The derived electron-density distribution, maximum electron-density paths, interaction lines and bond critical points along Ca...F and F...F contacts revealed the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The textbook notion that species such as CaF 2 consist of spherical ions has rarely been questioned, although there is evidence that either a multipole or a neutral-atom model may describe such compounds better than the conventional ionic model. 49,50 Electron and γ-ray diffraction have shown that there is non-sphericity of the valence electron density in KCl, LiF, and MgO. 51,52 Specifically for Ca 2+ , the formally empty d-orbitals can be partially populated to add substantial covalent bonding character to the cation–anion interactions, as, for example, in the putative Zintl-phase of CaSi 53 or the calcocenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The textbook notion that species such as CaF 2 consist of spherical ions has rarely been questioned, although there is evidence that either a multipole or a neutral-atom model may describe such compounds better than the conventional ionic model. 49,50 Electron and γ-ray diffraction have shown that there is non-sphericity of the valence electron density in KCl, LiF, and MgO. 51,52 Specifically for Ca 2+ , the formally empty d-orbitals can be partially populated to add substantial covalent bonding character to the cation–anion interactions, as, for example, in the putative Zintl-phase of CaSi 53 or the calcocenes.…”
Section: Introductionmentioning
confidence: 99%
“… 54 Here, utilizing HAR, we show that there is significant bond-directed non-spherical valence density present in the crystal structure of CaF 2 . 49 …”
Section: Introductionmentioning
confidence: 99%
“…used the term “protocovalent bond” for the situations in which the ELF bond basin is split at the equilibrium interatomic distance . It was observed for the F−F bond in the F 2 molecule,,, and recently also in the CaF 2 crystal . The bond nature in the F 2 molecule and the reasons for its low dissociation energy are still under debate .…”
Section: Resultsmentioning
confidence: 99%
“…[38] It was observed for the FÀF bond in the F 2 molecule, [28,38,39] and recently also in the CaF 2 crystal. [40] The bond nature in the F 2 molecule and the reasons for its low dissociation energy are still under debate. [41][42][43][44][45] The analysis with the domain-averaged Fermi-hole orbitals [46] suggested that at the equilibrium distance the FÀF bond in F 2 is already partially dissociated, [43] which supports our assumption about the connection between the split of the ELIÀD attractor and the instability of the corresponding bond.…”
Section: Electron Localizability Indicatormentioning
confidence: 99%
“…This is a much less time-consuming alternative to Bader's quantum theory of atoms in molecules space partitioning method (Bader, 1994) that we utilised for fluorite (Stachowicz et al , 2017) with an extension of the procrystal electron density for aspherical atomic contributions (Coppens, 1997). The latter approach, although computationally demanding, allows for a more detailed analysis of electron density distribution and corresponding physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%